Infectious agents and immune responses in schizophrenia: A case control study - Mustafa Mahmud, Mohammed Imad Al-Deen; Rafi, Berjees; Ali Khan, Umeed; Mohamed El Hady, Hassan (IIUM Medical Journal Malaysia, 2016)
Introduction: Exact causal mechanism of schizophrenia is still unknown; however, genetic and environmental factors are implicated in disease aetiology. The aim of the study is to determine the association of infectious agents cytomegalovirus and T.gondii along with immune cytokines IL-2, IL-6 and IFN-γ with schizophrenia. Methods: Ninety subjects participated in the study, 45 were patients diagnosed with schizophrenia, and the other 45 were a healthy control group. Qualitative and quantitative enzyme immunoassays were used for detection of antibodies and quantitation of cytokines respectively in subjects’ sera. Results: Both patients and control groups had similar CMV seroprevalence of 93.3% (42/45). Prevalence of anti T. gondii IgG antibodies were 53.3% and 64.4% among schizophrenic patients and controls respectively. No statistically significant difference was observed between patients and controls (p > 0.05). A significant difference (p<0.005) between mean serum Interleukin-2 levels in patients (14.7 pg/mL) and controls (33.5 pg/mL) was observed. No statistically significant difference (p>0.05) was found between the median IQR serum Interleukin-6 levels of patients (4.3 pg/mL) and controls (3.1 pg/mL). There was a significant difference (p< 0.001) in median IQR serum IFN – γ levels between patients (0.8 pg/mL) and the control group (4.9 pg/mL). Conclusions: No significant differences between schizophrenic patients and healthy controls with regard to previous infections with cytomegalovirus or T.gondii were observed. While significantly higher levels of proinflammatory cytokines IL-6 and IFN – γ among controls than patients might be an indication of weaker than normal immune responses in schizophrenic patients.